Engaging plant anatomy and local knowledge on the buriti palm (Mauritia flexuosa L.f.: Arecaceae): the microscopic world meets the golden grass artisan's perspective - Viana, Rebeca V. R.; Scatena, Vera L. [UNESP]; Eichemberg, Mayra T.; Sano, Paulo T. (Springer, 2018)
Considering that both Western Science and Local Knowledge Systems share a common ground-observations of the natural world-the dialogue between them should not only be possible, but fruitful. Local communities whose livelihoods depend on traditional uses of the local biodiversity not only develop knowledge about nature, making several uses of such knowledge, but, with that process, several inquiries about nature can be raised. Here we present our experience with the engagement of Western Science with golden grass artisan's knowledge about the buriti palm (M. flexuosa). We applied 25 semidirective interviews, combined with field diary and participative observation, in two quilombola communities from Jalapao region (Central-Brazil). One of the inquiries that emerged from the artisan's perspectives was about the differences between male and female buriti palms' fiber. We then engaged both local and scientific perspectives regarding this issue using plant anatomy as a dialogue instrument. Here we describe this experience and resort to Paulo Freire's ideas on dialogue to argue that, to integrate Western Science and Local Knowledge Systems in a collaborative and contextualized perspective, the research should be faced as a mutual learning practice.
Keywords: Local knowledge systems; Plant anatomy; Buriti palm; Dialogue; Jalapao; Golden grass handicraft